The wind in my hair : my fight for freedom in modern Iran - ʻAlīʹnizhād, Masīḥ, 1976-; Foroohar, Kambiz (Little Brown and Company/Hachette Book Group, 2018)
"An extraordinary memoir from an Iranian journalist in exile about leaving her country, challenging tradition, and sparking an online movement against compulsory hijab. A photo on Masih Alinejad's Facebook page: a woman standing proudly, face bare, hair blowing in the wind. Her crime: removing her veil, or hijab, which is compulsory for women in Iran. This is the self-portrait that sparked My Stealthy Freedom, a social media campaign that went viral. But Alinejad is much more than the arresting face that sparked a campaign inspiring women to find their voices. She's also a world-class journalist whose personal story, told in her unforgettably bold and spirited voice in The Wind in My Hair, is emotional and inspiring. She grew up in a traditional village where her mother, a tailor and respected figure in the community, was the exception to the rule in a culture where women reside in their husbands' shadows. As a teenager, Alinejad was arrested for political activism and then surprised to discover she was pregnant while in police custody. When she was released, she married quickly and followed her young husband to Tehran, where she was later served divorce papers, to the embarrassment of her religiously conservative family. She spent years struggling to regain custody of her only son and remains in forced exile from her homeland and her heritage. Following Donald Trump's immigration ban, Alinejad found herself separated from her child, who lives abroad, once again. A testament to a spirit that remains unbroken, and an enlightening, intimate invitation into a world we don't know nearly enough about, The Wind in My Hair is the extraordinary memoir of a woman who overcame enormous adversity to fight for what she believes in and to encourage others to do the same."--Dust jacket.